International diversification and risk of multinational banks: evidence from the pre-crisis period - Gulamhussen, M. A.; Pinheiro, C.; Pozzolo, A. F. (Journal of Financial Stability, 2014)
The recent financial crisis has clearly shown that the relationship between bank internationalization and risk is complex. Multinational banks can benefit from portfolio diversification, reducing their overall riskiness, but this effect can be offset by incentives going in the opposite direction, leading them to take on excessive risks. Since both effects are grounded on solid theoretical arguments, the answer of what is the actual relationship between bank internationalization and risk is left to the empirical analysis. In this paper, we study such relationship in the period leading to the financial crisis of 2007–2008. For a sample of 384 listed banks from 56 countries, we calculate two measures of risk for the period from 2001 to 2007 – the expected default frequency (EDF), a market-based and forward-looking indicator, and the Z-score, a balance-sheet-based and backward-looking measure – and relate them to the degree of banks’ internationalization. We find robust evidence that international diversification increases bank risk.